TEACHING LISTENING COMPREHENSION THROUGH TQLR (TUNE IN, QUESTION, LISTEN, REVIEW) STRATEGY TO THE TWELFTH GRADE STUDENTS OF SMA NEGERI 2 TEBING TINGGI - Linda Herlina (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
This study was to find out whether or not (1) there was a significant difference on the twelfth grade students’ listening comprehension between those who are taught by using TQLR strategy and those who are not at SMA Negeri 2 Tebing Tinggi, and (2) there was a significant impovement on the twelfth grade students’ listening comprehension between those who are taught by using TQLR and those who are not before and after the treatment at SMA Negeri 2 Tebing Tinggi. The result showed that (1) there was a significant difference on the twelfth grade students’ listening comprehension between those who are taught by using TQLR strategy and those who are not at SMA Negeri 2 Tebing Tinggi, and (2) there was a significant impovement on the twelfth grade students’ listening comprehension between those who are taught by using TQLR and those who are not before and after the treatment at SMA Negeri 2 Tebing Tinggi It means that there was significant difference on students’ listening comprehension taught by using TQLR strategy than students who are taught by using strategy used by teacher.